MicroRNA-34a: A Novel Therapeutic Target in Fibrosis - Zhao, Min; Qi, Qin; Liu, Shimin; Huang, Rong; Shen, Jiacheng; Zhu, Yi; Chai, Jing; Zheng, Handan; Wu, Huangan; Liu, Huirong (Frontiers in Physiology, 2022)
Fibrosis can occur in many organs, and severe cases leading to organ failure and death. No specific treatment for fibrosis so far. In recent years, microRNA-34a (miR-34a) has been found to play a role in fibrotic diseases. MiR-34a is involved in the apoptosis, autophagy and cellular senescence, regulates TGF-β1/Smad signal pathway, and negatively regulates the expression of multiple target genes, so as to affect the deposition of extracellular matrix and regulate the process of fibrosis. Some studies have explored the effect of miR-34a targeted therapy for fibrotic diseases. Therefore, miR-34a has specific potential in the treatment of fibrosis. This article reviews the important role of miR-34a in fibrosis, and provides the possibility for miR-34a as a novel therapeutic target in fibrosis.